Primary HSV-2 Infection in an Immunocompromised Patient Reveals High Diversity of Drug-Resistance Mutations in the Viral DNA Polymerase - Hanna Helena Schalkwijk; Sarah Gillemot; Emilie Frobert; Florence Morfin; Sophie Ducastelle; Anne Conrad; Pierre Fiten; Ghislain Opdenakker; Robert Snoeck; Graciela Andrei (Viruses, 2025)
Herpes simplex virus 2 (HSV-2) remains a significant cause of morbidity and mortality in immunocompromised individuals, despite the availability of effective antivirals. Infections caused by drug-resistant isolates are an emerging concern among these patients. Understanding evolutionary aspects of HSV-2 resistance is crucial for designing improved therapeutic strategies. Here, we characterized 11 HSV-2 isolates recovered from various body sites of a single immunocompromised patient suffering from a primary HSV-2 infection unresponsive to acyclovir and foscarnet. The isolates were analyzed phenotypically and genotypically (Sanger sequencing of viral thymidine kinase and DNA polymerase genes). Viral clone isolations, deep sequencing, viral growth kinetics, and dual infection competition assays were performed retrospectively to assess viral heterogeneity and fitness. Sanger sequencing identified mixed populations of DNA polymerase mutant variants. Viral clones were plaque-purified and genotyped, revealing 17 DNA polymerase mutations (K533E, A606V, C625R, R628C, A724V, S725G, S729N, I731F, Q732R, M789T/K, Y823C, V842M, R847C, F923L, T934A, and R964H) associated with acyclovir and foscarnet resistance. Deep-sequencing of the DNA polymerase detected drug-resistant variants ranging between 1 and 95%, although the first two isolates had a wild-type DNA polymerase. Some mutants showed reduced fitness, evidenced by (i) the frequency of variants identified by deep-sequencing not correlating with the proportion of mutants found by plaque-purification, (ii) loss of the variants upon passaging in cell culture, or (iii) reduced frequencies in competition assays. This study reveals the rapid evolution of heterogeneous drug-resistant HSV-2 populations under antiviral therapy, highlighting the need for alternative treatment options and resistance surveillance, especially in severe infections.